Helium loss, tectonics, and the terrestrial heat budget. - Oxburgh,ER; O'nions,RK (Science, 1987)
It has been known for the last decade that primordial helium incorporated in Earth at the time of its formation is still being degassed during the formation of new ocean crust at spreading ocean ridges. It is now clear that somewhat contrary to expectation, substantial degassing is also taking place through the continental crust. In western Europe the escape of mantle volatiles seems to occur largely where the crust is undergoing active extension. Although it is known that melting is the principal process for extracting and concentrating helium from the mantle at ocean ridges, the equivalent subcontinental process remains poorly understood. The same elements that are responsible for most of Earth's radiogenic heating (uranium and thorium) are also responsible for the generation of radiogenic helium. The present rate of mantle heat loss, however, is out of equilibrium with the rate of helium loss-too large by about a factor of 20. Either radiogenic helium is accumulated in the mantle while heat escapes or current models for the bulk chemistry of Earth are in error and much of the terrestrial heat loss is nonradiogenic.